Implementasi Sistem Absensi Menggunakan Qrcode Berbasis Client Server Di SMK N 1 Bengkulu Selatan - M. Azzahrul Ikhsan; Toibah Umi Kalsum; Hendry Alamsyah (Jurnal Media Infotama, 2024)
SMK N 1 Bengkulu Selatan is one of the vocational schools in Seluma Regency with Accreditation A which is located on Jl. A. Yani - Manna, Bengkulu Province. Currently the student attendance system still uses a manual method, namely by filling in or checking on the attendance sheet that has been provided, so that when checking attendance it will take time to collect attendance sheets and there are also attendance sheets that are no longer clear or legible so that attendance data will be lost. The attendance system using QRCode at SMK N 1 Bengkulu Selatan was built using the PHP programming language and MySQL database. Where in doing attendance by presenting each student's QRCode to a predetermined camera. Where this QRCode is based on the student's NIS, so that each student has their own QRCode. With this attendance system students, teachers and education personnel can see or check attendance at any time because attendance data is stored digitally in the database.